SISTEM MANAJEMEN INOVASI: ALTERNATIF PENDEKATAN BAGI TIPE INOVASI (Fokus Ekonomi, 2010)
Organizational require to use management system innovate to increase innovate. Management system is key to develop aspect innovate antagonistic which often times emerge, so that management system have to can manage duality from radical innovation and incremental innovation. Management system factor innovate is strategy innovate and portofolio. Selected management system have to emit a stream of direct the than strategy choice innovate and searched balance in portofolio. Incremental innovation is the way of to reach for as many as possible goods product or service which have there is without making signifikan or big invesment. Radical innovation is change of signifikan which by simultan influence business model and also company technology. Innovation type have to as according to company strategy. Deciding best innovation strategy as according to condition of internal emulation and eksternal.